UPAYA KONSERVASI KEANEKARAGAMAN HAYATI DIKAWASAN LINDUNG DI INDONESIA - Kuspriyanto, Kuspriyanto (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2015)
Indonesia is a country with a high level of biodiversity, which is characterized by the ecosystem, species in the ecosystem, and germplasm (genetic) which are in each type of ecosystem. Indonesia has become the central of biodiversity of the world and is known as mega-biodiversity country. High biodiversity is a natural wealth that can provide vital and strategic benefits, as the capital of national development. The purpose of this paper, among others, is to determine how biodiversity in Indonesia, to know how to control exotic species, to determine how the rehabilitation of animals, and to know the conservation efforts of ex-situ and in-situ. Biodiversity in premises belonging to the highest in the world, even much higher than America and Africa who have the same tropical climate. Factors that influence a new way for the invasion of exotic species, among others: the continental traffic, air traffic and agriculture. To control the invasion of exotic species, then these three factors must be considered. For the rehabilitation of animals then one is doing wildlife conservation efforts through the establishment of animal rescue center. Efforts to conserve biodiversity in situ include protection of representative examples of terrestrial and marine ecosystems and their flora and fauna therein. In-situ conservation is done in the form of natural reserve areas (nature reserves, wildlife reserves), national parks and protected areas. Ex-situ preservation can be done by keeping and breeding of plants and animals outside their natural habitats by collecting type, maintenance, and cultivation or captivity.